Estudo dos ligantes da proteína prion celular com ênfase em estress inducible protein 1: modificação pós-traducional, tráfego e sinalização - Fabiana Andrade Caetano (2010)
The cellular prion protein (PrPC) is a dynamic platform for the assembly of signalling modules at the cell surface. One of the best described ligand of PrPC is the co-chaperonine Stress Inducible Protein1 or STI1. This protein is secreted by astrocytes and interacts with PrPC at neuronal surface inducing neuritogeneses and neuroprotection through different signaling pathways. Although the mechanisms urderlying STI1 secretion are still poorly understood, it is believed that this process is important for modulation of neurotrophic functions mediated by STI1-PrPC interaction. The intracellulat STI1 also has an important role in the assembly of HSP70-HSP90 complex. Therefore, STI1 is considered a protein with intra and extracellular functions. To further investigate the mechanisms involved with STI1 functions, new ligands were identified in a yeast two hybrid screening. Amongst them, we found several proteins involved with the SUMOylation pathway, whose interaction with STI1 were confirmed in this work. We have shown that STI1 is SUMOylated by SUMO1 and SUMO3, and PIAS1 is the specific E3 SUMO ligase for this process. The interaction between STI1 and PIAS1 or SUMO3 promoted an increase in the nuclear localization of STI1. Once in the nucleus, STI1 was directed to PML bodies (Pro Myelocytic Leukaemia bodies) in a PIAS1 dependent process. In these structures STI1 was observed co-localized with SUMO1 and SUMO3. The cellular stress by Heat Shock did not induce alterations on STI1 intracellular distribution, even when proteins from the SUMOylation pathway were over expressed. On the other hand, we showed that the DNA damage by ionizing irradiation induced the translocation of STI1 to the nucleus, where this protein partly co-localizes with Foci. Combined, our results show that STI1 is preferentily modified by SUMO3 and PIAS1. STI1 targeting to PML bodies mediated by PIAS1 and nuclear translocation induced by genotoxic stress strongly suggest its participation in the DNA repair pathway. Considering the alteration in STI1 intracellular distribution induced by proteins from the SUMOylation pathway, new experiments are being peformed to better evaluate the involvement of this pathway in STI1 secretion. In relation to the role of STI1 in the extracellular environment, we have shown that STI1 binds to PrPC at the cell surface and induces its internalization. This process was specific and critical for regulation of ERK1/2, but not PKA activation, which is mediated by STI1-PrPC interaction. STI1 was also internalized by cells in a PrPC-independent way. Using real-time microscopy and several endocitic markers, we showed that STI1 is internalized by two main pathways: part of STI1 is endocited through a lipid raft-dependent pathway, whereas another fraction is internalized via a clathrin-mediated pathway. Once internalized, STI1 takes a distinct intracellular route from that described for PrPC. STI1 is directed to acidic vesicles bypassing early endossomes. Real time images of GFP-PrPC transfected cells perfused with fluorescent STI1 showed that the interaction between these proteins at the cell surface and in vesicles has a transient nature, suggesting that the trafficking of STI1 regulates the duration of signalling through PrPC. By using endocytosis inhibitors (dynamin K44A and AP180-C), we were able to visualize strong co-localization between STI1 and PrPC at the plasmatic membrane. PrPC endocytosis occurs through interaction with the membrane receptor LRP1. We used the LRP1 ligand RAP to block its interaction with PrPC. We noticed the block of the ERK1/2 activation mediated by STI1-PrPC interaction in cells treated with RAP. This result suggests that LRP1 can be part of the transmembrane complex connecting the extracellular stimulus with the intracellular signalling. A¥â peptides are the major culprits in Alzheimer.s disease and have recently been shown to bind to PrPC. We examined if A¥â oligomers affected PrPC trafficking. We find that in contrast to the STI1 effect, A¥â induced an increase in PrPC at cell surface, by blocking the constitutive endocytosis of PrPC. New experiments will be necessary to elucidate the implication of this result upon neurotoxicity mediated by A¥â peptids. In conclusion, our results show that STI1 has different roles in regulation of CNS. Moreover, PrPC trafficking seems to be a dynamic mechanism which can be quickly regulated by several ligands to modulate neuronal homeostasis. These results suggest that STI1 and PrPC have unantecipated roles in neuronal function.